Christmas - Schauffler, Robert Haven, 1879-1964 (Salt Lake City, UT : Project Gutenberg, 2006)
"Christmas: Its Origin, Celebration and Significance As Related in Prose and Verse" edited by Robert Haven Schauffler is an anthology that highlights the rich variety of literature associated with Christmas, likely compiled in the early 20th century. The book encompasses poems, essays, and short stories that explore the origins of the holiday, its celebrations, and its deeper significance. This collection aims to present the festive spirit of Christmas through various artistic expressions, making it suitable for both educational and leisurely reading. The opening of the anthology introduces readers to its purpose, explaining that it gathers a treasure of Christmas literature$1 (Bpoems, hymns, and stories, alongside a historical and cultural appreciation of the holiday. It discusses the evolution of Christmas from ancient pagan traditions to its place within Christian culture, touching upon various customs and significances around the world. The initial selections include notable writings like the famous editorial "Is There a Santa Claus?" from the New York Sun, as well as evocative poems like "O Little Town of Bethlehem" by Phillips Brooks, setting the tone for a work that not only celebrates the holiday but also reflects on its enduring impact on humanity. (This is an automatically generated summary.)s
Release date is 2006-07-25
E-text prepared by David Starner, Jeffrey Johnson, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Christmas -- Poetry; Christmas -- Literary collections